Paradigma Hikmah Dalam Fatwa DSN-MUI Tentang Janji (Wa’Ad) Dalam Transaksi Keuangan Dan Bisnis - Aswati, Aswati; Muhaini, Akhmad; Ma'rufi, Anwar (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In the current global economic context, the idea of promises (wa'ad), in business and financial dealings that are Islamic has become increasingly important amidst ongoing uncertainty and market dynamics. The global economy is under significant pressure due to geopolitical tensions, high inflation, and currency fluctuations, posing new challenges in financial transactions. This situation demands greater certainty and transparency to protect all parties involved, with Sharia principles playing a crucial role in ensuring that transactions are conducted fairly and in accordance with Sharia. Despite the clear guidelines provided by the DSN-MUI fatwa on wa'ad, practical challenges remain in implementing wisdom principles such as maslahah (public interest), justice, ease, benefit, and freedom. This study employs a qualitative library research method to see how these ideas are applied in the DSN-MUI fatwa. Primary data is sourced from DSN-MUI fatwa documents, while secondary data includes academic literature and previous studies. Data collection involves documentation and content analysis, with validity ensured through data triangulation. According to the results, the DSN-MUI fatwa effectively integrates wisdom principles, promoting justice, benefit, and Sharia compliance in transactions. The fatwa guidelines enhance the implementation of wa'ad, ensuring alignment with core Sharia values and making a positive contribution to the Islamic financial system.